Effect of Combination of Plant Types on Attack of Spodoptera Frugiperda J. E Smith - Azwana Azwana; Selvina Selvina; Suswati Suswati (Budapest International Research in Exact Sciences (BirEx) Journal, 2022)
Spodoptera frugiperda J. E. Smith is a new pest in maize plantations originating from America and has spread to Sumatra in mid-2019. The aim of this study was to determine the combination of host plant species most favored by S. frugiperda larvae. The types of plants tested were sweet corn, hybrid corn, white corn, land rice, soybeans, green beans, and elephant grass. Each plot was combined with 3 types of plants so that there were 16 plots with 2 replications. The research was conducted using a descriptive method and each research plot was covered with mosquito nets. The larvae of S. frugiperda used were rearing 3 instar larvae and came from separate maize plantations. The results showed that S. frugiperda liked the combination of plants from the Gramineae family. The combination of plants favored by S. frugiperda was consecutively A (sweet corn, white corn and hybrid corn) with 33.8% attack intensity, E (sweet corn, soybean and land rice) 13% attack intensity, C (maize) white, soybean and elephant grass) attack intensity 12.8%, B (sweet corn, green beans and rice) attack intensity 12.3%, G (hybrid corn, soybean and rice) attack intensity 11.5%, D, F and treatment H. The number of pupae was also found in the combination treatment of corn, rice and elephant grass and not found in soybean and mung bean plants.